Pengaruh Penerapan E-Filing terhadap Kepatuhan Wajib Pajak (Studi Kasus pada Anggota Koperasi LKMS Ukhuwah Bintang Ihsani Kota Bengkulu) - Tassha Saskia; Nurul Hak; Herlina Yustati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of the study was to find out the effect of the implementation of e-filing on taxpayer compliance with members of the Bintang Ihsani LKMS Cooperative Bengkulu The research approach is a quantitative approach where researchers go directly to the field The type of data u.sed is pri.mary data by filling out the questionnaire given. The res.ults showed that the sig va.lue of 0.022 < 0.05 means that the iplementation of e-filling on tax compliance has an effect.